2015
DOI: 10.1021/acschemneuro.5b00040
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Decline in Brain and Hepatic Clearance of Amyloid-Beta is Rectified by the Cholinesterase Inhibitors Donepezil and Rivastigmine in Rats

Abstract: In Alzheimer’s disease (AD), accumulation of brain amyloid-β (Aβ) depends on imbalance between production and clearance of Aβ. Several pathways for Aβ clearance have been reported including transport across the blood-brain barrier (BBB) and hepatic clearance. The incidence of AD increases with age and failure of Aβ clearance correlates with AD. The cholinesterase inhibitors (ChEIs) donepezil and rivastigmine are used to ease the symptoms of dementia associated with AD. Besides, both drugs have been reported to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 56 publications
4
52
0
Order By: Relevance
“…Following to our previous findings [13], this study aims to investigate the question “how changes in P-gp expression would affect rivastigmine therapeutic effect, including Aβ lowering effect, neuroprotection and anti-inflammatory effect using APPSW mice that carry APP transgene and P-gp WT (APP/mdr1 +/+ ), P-gp one copy (APP/mdr1 +/− ), or P-gp knockout (APP/mdr1 −/− ) mice. Overall findings suggest that P-gp mediates the non-cholinergic effects of rivastigmine, and that understanding various mechanisms of action of rivastigmine is important to optimize its clinical utility for AD patients.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Following to our previous findings [13], this study aims to investigate the question “how changes in P-gp expression would affect rivastigmine therapeutic effect, including Aβ lowering effect, neuroprotection and anti-inflammatory effect using APPSW mice that carry APP transgene and P-gp WT (APP/mdr1 +/+ ), P-gp one copy (APP/mdr1 +/− ), or P-gp knockout (APP/mdr1 −/− ) mice. Overall findings suggest that P-gp mediates the non-cholinergic effects of rivastigmine, and that understanding various mechanisms of action of rivastigmine is important to optimize its clinical utility for AD patients.…”
Section: Introductionmentioning
confidence: 53%
“…Rivastigmine is a dual cholinesterase inhibitor which acts by inhibiting degradation of ACh at synapses and improving cholinergic transmission that is known to be impaired in AD. Recently, we have shown that FDA-approved drugs for AD modulate Aβ transport by up-regulating the expression of P-gp and LRP1 at the BBB and hepatocytes [13]. Among those drugs, we found that rivastigmine was most efficient to induce the expression of P-gp and LRP1 in the brains of aged rats and were associated with reduced levels of endogenous Aβ 40 and Aβ 42 [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a reversible AChE inhibitor that binds to the peripheral anionic site, and does not affect BChE. It has symptomatic effects in AD treatment but, like rivastigmine, it also appears to delay the deposition of amyloid plaque (see [94]) or to enhance plaque removal [121]. It has a relatively long half-life in vivo (about 70 h), reducing the need for too frequent dosage.…”
Section: Inhibitors Of Acetylcholinesterase (Ache) and Butyrylcholinementioning
confidence: 99%
“…In addition to these pathologies, the decline in level of neurotransmitter acetylcholine (ACh) and cholinergic dysfunction are also observed in AD [4e6]. Most of AD drugs, currently available on the market, which are approved by FDA, have been developed to increase ACh levels and to improve the cognitive function by inhibiting acetylcholinesterase (AChE, EC 3.1.1.7) [7]. However, these treatments become ineffective as disease progresses since they do not prevent the synaptic loss.…”
Section: Introductionmentioning
confidence: 99%